Is Reference Essential to Meaning?. (3rd December 2020) - Richard, Mark
Most linguists and philosophers will tell you that whatever meaning is, it determines the reference of names, the satisfaction conditions of nouns and verbs, the truth conditions of sentences; in linguist speak, meaning determines semantic value. So a change in semantic value implies a change in meaning. So the semantic value a meaning determines is essential to that meaning: holding contributions from context constant, if two words have different semantic values they cannot mean the same thing. If this is correct, then in a fairly straightforward sense reference is essential to meaning. In this paper I argue that reference is not essential to meaning by giving an example in which groups in different circumstances use a phrase with the same meaning but a different reference.